Scope and Justification of the Right of Publicity - Sheff, Jeremy (The Columbia Journal of Law & the Arts, 2019)
Thank you to Professor June Besek, and thanks to everyone here at Columbia for the invitation. June, to correct one of your introductions here—Mark McKenna is too humble to say so, but in addition to being a widely recognized scholar, he was elected yesterday to the American Law Institute, which is well deserved given his immense contributions to Intellectual Property Law scholarship. Mark and I have talked about this topic, in part in preparation for today, and so a lot of what I say is going to reflect some of what he has said, and I think that is fine. (There are worse things you can say about a scholar than, “oh, he sounds just like McKenna.”) One of the things that has come up in the discussions this morning and on this panel—which considers the scope of the Intellectual Property right of the Right of Publicity, and whether it is an Intellectual Property right or not—is the relationship between scope and justification. Mark’s comments suggest that there is no such relationship with respect to the Right of Publicity; or, that at least it is loose. The biggest contribution of Jennifer’s excellent book is to encourage us to think about the rights of publicity and the rights of privacy as different things that have— for odd historical reasons, some of them with a purpose—been lumped together. And that we ought to try to think about them more separately and their justifications more separately.